PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA DAN MOTIVASI KERJA TERHADAP IMPLEMENTASI PENGELOLAAN KEUANGAN DAERAH PADA DINAS PENDAPATAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN WAKATOBI - Darmawan, Lukman (JURNAL AKUNTANSI, 2016)
This research was conducted in the department of finance and asset management revenue district of wakatobi in order to determine the influence of human resorce development and motivation to work towards the implementation of financial and asset management district wakatobi.The sample in this study is the overall revenue department personnel and financial management of local assets by 39 respondents, which is determined by the sampling technique is the method census (complete enumeration). Furthermore, the data were analyzed using multiple linear method assited. The results of study indicate that partial human resource development and work motivation was not significant positive effect on the implementation of the financial management area. As well as the motivation to work significant positive effect on the implementation of the financial management area. Simultaneously that human resorce development and motivation significant positive effect on the implementation of financial and asset management area. Keywords : Human Resource Development and Motivation & Implementation of Financial and Asset Management.